The Impact of Covid-19 Towards Human Security - Iqbal Ramadhan (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2021)
The emergence of coronavirus at the end of 2019 caused the world to fall into a global pandemic. It cannot be denied that the phenomenon of the Covid-19 pandemic caused a downturn in the global economy. The threat of the Covid-19 pandemic has endangered social aspects and has also destabilized the political and economic life of all countries. Covid-19 has an impact on human security around the world. The concept of human security essentially emphasizes human freedom from fear. Through the concept of human security, this article seeks to explain how people are classified as vulnerable objects. Their lives could be threatened by Covid-19. The author uses a qualitative methodology with case study techniques to address this issue. The analysis in this article shows that poor, undernourished people who do not have access to sanitation and health services live in densely populated areas and people with comorbidities are particularly vulnerable to exposure to Covid-19. The conclusion of this research is that the government needs to give priority to these vulnerable communities. They are the entities that need to be protected from the threat posed by Covid-19.AbstrakMunculnya virus corona di penghujung tahun 2019 menyebabkan dunia terjerumus ke dalam pandemi global. Tak bisa dipungkiri, fenomena pandemi Covid-19 menyebabkan perlambatan ekonomi global. Ancaman pandemi Covid-19 telah membahayakan aspek sosial dan juga mengguncang kehidupan politik dan ekonomi semua negara. Covid-19 berdampak pada keamanan manusia di seluruh dunia. Konsep keamanan manusia pada dasarnya menekankan kebebasan manusia dari rasa takut. Melalui konsep human security, artikel ini berusaha menjelaskan bagaimana manusia diklasifikasikan sebagai objek yang rentan. Hidup mereka bisa terancam oleh Covid-19. Penulis menggunakan metodologi kualitatif dengan teknik studi kasus untuk mengatasi masalah ini. Analisis dalam artikel ini menunjukkan bahwa orang miskin dan kurang gizi yang tidak memiliki akses ke sanitasi dan layanan kesehatan tinggal di daerah padat penduduk dan orang dengan penyakit penyerta sangat rentan terhadap paparan Covid-19. Kesimpulan dari penelitian ini adalah bahwa pemerintah perlu memberikan prioritas kepada masyarakat rentan tersebut. Mereka adalah entitas yang perlu dilindungi oleh pemerintah dari ancaman Covid-19.